2003
DOI: 10.1007/s00429-003-0315-8
|View full text |Cite
|
Sign up to set email alerts
|

A point mutation in bioactive RNA results in the failure of mutant heart correction in mexican axolotls

Abstract: Ambystoma mexicanum is an intriguing animal model for studying heart development because it carries a mutation in gene c. Hearts of homozygous recessive (c/c) mutant embryos do not contain organized myofibrils and fail to beat. The defect can be corrected by organ-culturing the mutant heart in the presence of RNA from anterior endoderm or endoderm/mesoderm-conditioned medium. By screening a cDNA library made of total conditioned medium RNA from normal axolotl embryonic endoderm, we isolated a single clone (MIR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 40 publications
2
40
0
Order By: Relevance
“…The uniqueness of MIR is that in addition to being involved in cTnT splicing, it also can increase the total cTnT mRNA concentration in the cells. We have already shown that MIR is capable of binding with one or more proteins present in axolotl hearts [17]. Also, we have already reported that in mutant axolotl hearts MIR is expressed.…”
Section: The Hearts Of Normal Embryos (+/+) Have a Much Higher Expresmentioning
confidence: 87%
See 4 more Smart Citations
“…The uniqueness of MIR is that in addition to being involved in cTnT splicing, it also can increase the total cTnT mRNA concentration in the cells. We have already shown that MIR is capable of binding with one or more proteins present in axolotl hearts [17]. Also, we have already reported that in mutant axolotl hearts MIR is expressed.…”
Section: The Hearts Of Normal Embryos (+/+) Have a Much Higher Expresmentioning
confidence: 87%
“…All dissections were carried out under a dissecting microscope. Hearts were then placed in 96 U-well shaped plates containing Steinberg's solution for liposome-mediated RNA transfection following our published methods [15][16][17][18]. Mutant hearts were divided into two groups: those treated with sense MIR and those treated with antisense MIR.…”
Section: Organ Cultures For Embryonic Heartsmentioning
confidence: 99%
See 3 more Smart Citations